Effect of Extracts of Artemisia diffusa Against Plasmodium berghei - Taherkhani, Mahboubeh; Rustaiyan, Abdolhossein; Nahrevanian, Hossein (Asian Journal of Chemistry, 2017)
The authors retract the above article for violations of the ethical guidelines to publication. This article was published without the knowledge or consent of the author/s. As a result, the authors retract this manuscript.